Determinants of Subjective Well-being: Do we Really Know What Makes People Happy? A Study on Rasht Metropolis, North of Iran - Sepideh Kaveh; Abbas Assari Arani; Sajjad Faraji Dizaji; Seyed Hasan Hoseini (Gonabad University of Medical Sciences, 2021)
Background: Background: Recently, along with traditional economic indicators, policymakers are increasingly dealing with Subjective Well-Being (SWB) as an evaluation criterion of their performance and as an index for the population's psychology health. This was done to define different determinants of SWB with a focus on some specific aspects of the living area. Also, this article investigateed the effect of urban and outskirts area on SWB. Method: This study is a cross-sectional study based on a structured interview and the samples (219 people ) were selected by a two-stage cluster sampling method in 2018 in Rasht city, a metropolis in Iran. In designing the local questionnaire, Gallup's Global Emotions questionnaire has been used. Two main contributions of this study are defining culturized and proper indices for measuring SWB, and the financial status of people while Iranian people used to understate their real income. Data analysis was conducted using STATA 14.2 applying Descriptive statistics, Correlation study, Ordered Probit regression Method.  Results: Results show that improving the socio-economic status of people improve SWB. Having financial satisfaction, satisfaction with leaving area, being tenure, and living in more spacious residency have positive effects on SWB. Also, the city dwellers were found to have higher SWB (5.23 out of 7) than outskirt dwellers (4.9 out of 7) while keeping the other factors to be constant. They reported the same differences in positive feelings and negative feelings indices. Conclusion: The welfare policies should be revised to improve the financial status of all people, and increase the access to urban facilities for outskirts' dwellers.